The Voices of Indonesian Students on the Use of English Translation of the Holy Quran as an Authentic Material Resource to Teach Reading - Sumarsono, Puji (Lingual Journal of Language and Culture, 2019)
English translation of the Holy Quran has been utilized as an authentic material to teach and learn English (Sumarsono, 2016). A skill which is directly related to this issue is reading through a genre based-approach by exploring narrative texts in the Holy Quran (Sumarsono, 2017). Considering that these previous researches have developed teaching methodology and also teaching materials, it is crucial to understand the students’ voices concerning the use of this methodology and materials. The importance of this study is to provide feedback and improve the use of this methodology and materials. This study applied qualitative as it intended to understand and describe the phenomenon deeply. An instrument which was applied was an interview and the interviewees were the students who were joining a class using this methodology and teaching materials. The students have positive views on the use of English Translation of the Holy Quran as an authentic material resource to teach reading. This methodology has two crucial roles in the development of knowledge and faith.